Облагораживание древесины - Берсенев Альвиан Павлович (Книжное издательство, 1960)
Экземпляры: КХ (20120914) / Инвентарный номер: 285199 / Цена: 3.20 / Сис.шифр: 674 / Авт.знак: Б 51 / ГРНТИ: 66 / ББК: 37